ICT adoption and productivity in developing countries: new firm level evidence from Brazil and India - Rakesh Basant; Simon Commander; Rupert Harrison; Naércio Aquino Menezes Filho (Institute for the Study of Labor (IZA), 2006)
This paper uses a unique new data set on nearly a thousand manufacturing firms in Brazil and India to investigate the determinants of ICT adoption and its impact on performance in both countries. The descriptive evidence shows that Brazilian firms on average use ICT more intensively than their Indian counterparts but changes over time have been rather similar in both places. Within countries ICT intensity is strongly related to size, ownership structure, share of administrative workers and education. The econometric evidence documents a strong relationship between ICT capital and productivity in both countries, even after controlling for several other factors, including firm-specific fixed-effects. The rate of return of ICT investment seems to be much larger than usually found in more developed countries. Specific types of organisational changes matter for the return of ICT, but only for high adopters. Firms report several constraints to ICT investment in both countries and power disruption seems to significantly depress adoption and returns to ICT expenditures in India. This may be indicative of the impact of a cluster of poor institutions and/or infrastructure on performance.
Keywords: 330